DIFFERENCE OF TUMOR MASS IN STADIUM IIB-IIIB SQUAMOUS CELL CERVICAL CANCER PATIENTS WHO UNDERWENT PACLITAXEL CISPLATIN AND PACLITAXEL CARBOPLATIN CHEMOTHERAPY AT SANGLAH HOSPITAL DENPASAR - Noviyani, Rini; Indrayathi, Putu Ayu; Budiana, I. Nyoman Gede; Suwiyoga, Ketut; Putri, Septiara (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: One of the parameters to measure the efficacy of the use of platinum based chemotherapy was the difference of tumor mass. Unfortunately, there was limited data about the use of rational chemotherapy medicine for cervical cancer patients at Sanglah Hospital. Therefore, research to find more data about the difference of tumor mass was necessary. Â Method: A prospective observational research conducted at Sanglah Hospital from January until August 2016 by using consecutive sampling method. Patients qualified for the inclusive criteria were separated into two groups, paclitaxel cisplatin and paclitaxel carboplatin. Tumor mass data was gathered from before chemotherapy I and after chemotherapy VI by using USG 2D LOGIQ V5. Data analysed was performed with SPSS 20.0 for windows with a 95% confidence level using Wilcoxon test and Mann Whitney test. Result: The mean value of tumor mass for patients in paclitaxel cisplatin regimen group before chemotherapy I and after chemotherapy VI were 68.91+7.41 cm3 and 10.62+6.82 cm3 respectively (p value=0.018). The mean value of tumor mass for patients in paclitaxel carboplatin regimen group before chemotherapy I and after chemotherapy VI were 53.44+52.25 cm3 and 9.18 + 8.23 cm3 respectively (p value=0.007). Meanwhile, the mean value of difference in tumor mass in paclitaxel cisplatin and paclitaxel carboplatin group was -58.29 + 49.93 cm3 and -44.26 + 51.48 cm3 respectively (p value=0.242).Â Â Â Â Â Â Â Conclusion: This research shows that there was a significant difference of tumor mass before chemotherapy I and chemotherapy VI in both regimen groups. There was a bigger decrease of tumor mass in patients from paclitaxel cisplatin chemotherapy group compared to paclitaxel carboplatin group, but not significantly different.Â